Detection of IgG and IgM Antibodies to Rubella Virus in Misurata Population (مجلة البحوث الأكاديمية, 2024)
Background: Although a single dosage of the rubella-containing vaccine (RCV) can offer long-lasting protection against rubella, the disease still affects both adults and children in many parts of the world.Objectives: This study was designed to determine the seroprevalence of IgG and IgM antibodies to rubella virus in the Misurata population, thus, determining the proportion of individuals at risk of infection, as well as to develop preventive measures for congenital rubella syndrome (CRS).Materials and Methods: 198 participants were randomly selected for the study, and the IgG and IgM antibodies specific to the rubella virus were evaluated using the ELISA technique.Results: The seroprevalence of rubella IgG antibodies was 81.3% and therefore these individuals have good immunity against the rubella virus, while the proportion of people exposed to rubella virus was rather high 18.7%. And the results showed that 2.5% have IgM antibodies against rubella (recent infection). The highest rate of rubella IgG antibodies was in the age groups 1 to 15 years and those who were older than 46. Females between the ages of 16 and 45 years are highly susceptible to German measles.Conclusion:  The National Health Service must work to eradicate the rubella virus, which includes immunizing all vulnerable individuals.
Keywords: Rubella; Germany measles; Antibodies; Immunoglobulin; Misurata